Genetic control of root architectural plasticity in maize - Schneider, Hannah M; Klein, Stephanie P; Hanlon, Meredith T; Nord, Eric A; Kaeppler, Shawn; Brown, Kathleen M; Warry, Andrew; Bhosale, Rahul; Lynch, Jonathan P (Journal of experimental botany, 2020)
Root architectural phenes have heritable and plastic responses, and genetic loci associated with stress and environmental plasticity are distinct from loci controlling phenotypic expression in water-stress and well-watered conditions. Abstract Root phenotypes regulate soil resource acquisition; however, their genetic control and phenotypic plasticity are poorly understood. We hypothesized that the responses of root architectural phenes to water deficit (stress plasticity) and different environments (environmental plasticity) are under genetic control and that these loci are distinct. Root architectural phenes were phenotyped in the field using a large maize association panel with and without water deficit stress for three seasons in Arizona and without water deficit stress for four seasons in South Africa. All root phenes were plastic and varied in their plastic response. We identified candidate genes associated with stress and environmental plasticity and candidate genes associated with phenes in well-watered conditions in South Africa and in well-watered and water-stress conditions in Arizona. Few candidate genes for plasticity overlapped with those for phenes expressed under each condition. Our results suggest that phenotypic plasticity is highly quantitative, and plasticity loci are distinct from loci that control phene expression in stress and non-stress, which poses a challenge for breeding programs. To make these loci more accessible to the wider research community, we developed a public online resource that will allow for further experimental validation towards understanding the genetic control underlying phenotypic plasticity.